Androgen excess and diagnostic steroid biomarkers for nonclassic 21-hydroxylase deficiency without cosyntropin stimulation. Issue 1 (July 2020) - Turcu, Adina F; El-Maouche, Diala; Zhao, Lili; Nanba, Aya T; Gaynor, Alison; Veeraraghavan, Padma; Auchus, Richard J; Merke, Deborah P
Abstract : Objectives: The clinical presentation of patients with nonclassic 21-hydroxylase deficiency (N21OHD) is similar with that for other disorders of androgen excess. The diagnosis of N21OHD typically requires cosyntropin stimulation. Additionally, the management of such patients is limited by the lack of reliable biomarkers of androgen excess. Herein, we aimed to: (1.) compare the relative contribution of traditional and 11-oxyandrogens in N21OHD patients and (2.) identify steroids that accurately diagnose N21OHD with a single baseline blood draw. Design: We prospectively enrolled patients who underwent a cosyntropin stimulation test for suspected N21OHD in two tertiary referral centers between January 2016 and August 2019. Methods: Baseline sera were used to quantify 15 steroids by liquid chromatography-tandem mass spectrometry. Logistic regression modeling was implemented to select steroids that best discriminate N21OHD from controls. Results: Of 86 participants (72 females), median age 26, 32 patients (25 females) had N21OHD. Age, sex distribution, and BMI were similar between patients with N21OHD and controls. Both testosterone and androstenedione were similar in patients with N21OHD and controls, while four 11-oxyandrogens were significantly higher in patients with N21OHD (ratios between medians: 1.7 to 2.2, P  < 0.01 for all). 17α-Hydroxyprogesterone (6.5-fold), 16α-hydroxyprogesterone (4.1-fold), and 21-deoxycortisol (undetectable in 80% of the controls) were higher, while corticosterone was 3.6-fold lower in patients with N21OHD than in controls ( P  < 0.001). Together, baseline 17α-hydroxyprogesterone, 21-deoxycortisol, and corticosterone showed perfect discrimination between N21OHD and controls. Conclusions: Adrenal 11-oxyandrogens are disproportionately elevated compared to conventional androgens in N21OHD. Steroid panels can accurately diagnose N21OHD in unstimulated blood tests.